Climate change, health risks, and vulnerabilities in Burkina Faso: a qualitative study on the perceptions of national policymakers - Sorgho, Raissa; Jungmann, Maximilian; Souares-Coutant, Aurélia; Danquah, Ina; Sauerborn, Rainer (International journal of environmental research and public health, 2021)
Climate change (CC) constitutes one of the greatest threats to human health, and requires political awareness for effective and efficient adaptation planning. This study identified the perceptions of climate change and health adaptation (CC&H) among relevant stakeholders, decision-makers, and policymakers (SDPs) in Burkina Faso (BF) by determining their perceptions of CC, of related health risks and vulnerabilities, and of CC impacts on agriculture and food security. We carried out 35 semi-structured, qualitative in-depth interviews with SDPs, representing national governmental institutions, international organizations, and civil society organizations. The interviews were analyzed using content analysis. SDPs shared similar perceptions of CC and concurred with three ideas (1) CC is a real and lived experience in BF; (2) the population is aware of climatic changes in their environment; (3) CC is intertwined with the agricultural and economic development of the country. SDPs identified biodiversity loss, floods, droughts, and extreme heat as posing the highest risk to health. They elaborated five exposure pathways that are and will be affected by CC: water quality and quantity, heat stress, food supply and safety, vector borne diseases, and air quality. In conclusion, SDPs in Burkina Faso are highly aware of CC hazards, relevant health exposure pathways, and their corresponding health outcomes. Mental health and the interplay between social factors and complex health risks constitute perception gaps. SDPs perceived CC&H risks and vulnerabilities align with current evidence.